Civil society and social responsibility in higher education : international perspectives on curriculum and teaching development - Sengupta, Enakshi; Blessinger, Patrick; Mahoney, Craig (Emerald Publishing Limited, 2020)
As an increasing number of universities across the world focus efforts on giving back to the communities they exist in, there is now a growing appetite for information, examples, and case studies of best practice for social responsibility in Higher Education. This volume explores different angles of sustainability, university corporate social responsibility, and the role of civil society in the context of education, with a focus on curriculum development and teaching. The chapters provide international examples of new and innovative intiatives, focusing on areas including eliminating racism in nursing education, teaching writing for advocacy and active citizenship, and several examples of service learning in different contexts. The chapters also importantly provide theoretical frameworks for teaching sustainability in Higher Education. This book will prove an invaluable resource for those looking to reorienting curriculums, develop programs and modules, and implement innovative teaching methods which integrate sustainability and civil society into their institutions and educational programmes.
Includes indexes.
Keywords: Social responsibility of business.; Civil society.; Education, Higher.; Business & Economics -- Business Communication -- General.; Business ethics & social responsibility.; elektronické knihy; electronic books